The Dynamics of Imkan ar-Rukyat Criteria in Indonesia: Comparing Muhammad Mansur's Thought in Kitab Mizan al-I'tidal with the Neo-MABIMS Criteria - Muhammad Roihan Dliyaul Haq; Ahmad Adib Rofiuddin (Astroislamica: Journal of Islamic Astronomy, 2026)
Crucial differences in determining the beginning of the Hijri months, such as Ramadan, Shawwal, and Dhu al-Hijjah in Indonesia, are often triggered by a methodological dichotomy among Islamic organizations. This divergence is distinctly evident between the rukyat (lunar observation) method guided by Nahdlatul Ulama and the hisab (astronomical calculation) method adopted by Muhammadiyah. As an integrative solution, the concept of imkan ar-rukyat (possibility of sighting) emerges to bridge these two approaches through scientific lunar visibility criteria. Based on this reality, this study aims to conduct an in-depth examination of the dynamics of the imkan ar-rukyat criteria in Indonesia by comparing Muhammad Mansur's thoughts in the Kitab Mizan al-I'tidal with the neo-MABIMS criteria. This research employs a library research method utilizing a historical-comparative approach and descriptive analysis techniques. Primary data were extracted from the Kitab Mizan al-I'tidal, while secondary data were sourced from official MABIMS policy documents and Ministry of Religious Affairs regulations. The results reveal that Muhammad Mansur strongly rejected the rigid establishment of a lunar altitude threshold, such as at 7 degrees. Instead, he viewed imkan al-ru'yah as a dynamic and naturalistic concept grounded in continuous empirical observation, evidenced by testimonies of lunar sightings below 7° in various regions of Java. This dynamic paradigm aligns with the adaptive nature of the MABIMS criteria, which evolved from the old standard (altitude 2°, elongation 3°, moon age 8 hours) to the neo-MABIMS criteria (altitude 3° and elongation 6.4°) implemented since 2022. The government, through the Ministry of Religious Affairs, optimizes these criteria as a unifying instrument for the Muslim community. In conclusion, there is a paradigmatic continuity between the Nusantara astronomical turats (heritage) and contemporary criteria, affirming that lunar visibility standards remain open to revision in line with advancements in science and technology.